Uji Toksisitas Akut Instalasi Pengolahan Air Limbah (Ipal) Komunal X Kota Pekanbaru Menggunakan Daphnia Magna (Dhapnia sp) Dengan Metode Whole Effluent Toxicity (WET) - Vayolla Syakirah Karil; Shinta Elystia; Gunadi Priyambada (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
X Communal Wastewater Treatment Plant (WWTP) in Pekanbaru City is one of the solutions in processing domestic waste water so that it is safe before being discharged into waters. However, the WWTP effluent test results showed the value of COD, TSS, and Ammonia that exceed the quality standard. So there is a need for WET (Whole Effluent Toxicity) testing which is one way to monitor the performance of Wastewater Treatment Plant. This research aims to determine the value of LC50, TUa and analyze the connection between the quality of waste water and the level of toxicity in waste water. Acute toxicity tests were performed by static methods within 96 hours using Daphnia Magna test animals. Mortality of Daphnia magna were analyzed using Probit Method. The value of LC50 is 5,719% and TUa value is 17,486 with category III that means wastewater is on High Acute Toxicity. Measured COD, TSS, Ammonia, and Oil & Fat parameters affect the mortality of test animals, where the value of each of these parameters is directly proportional to the death rate of Daphnia magna. Keywords: Toxicity Test, Communal WWTP, Daphnia magna, WET, LC50.